2016
DOI: 10.3109/14756366.2016.1161620
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases (MMPs), the main extracellular matrix (ECM) enzymes in collagen degradation, as a target for anticancer drugs

Abstract: The main group of enzymes responsible for the collagen and other protein degradation in extracellular matrix (ECM) are matrix metalloproteinases (MMPs). Collagen is the main structural component of connective tissue and its degradation is a very important process in the development, morphogenesis, tissue remodeling, and repair. Typical structure of MMPs consists of several distinct domains. MMP family can be divided into six groups: collagenases, gelatinases, stromelysins, matrilysins, membrane-type MMPs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
625
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 804 publications
(641 citation statements)
references
References 44 publications
8
625
1
7
Order By: Relevance
“…To investigate whether BITRAP could modulate the cytokine level in Th17 cells, CD4 + T cells were cultured with BITRAP under Th17-polarizing condition for 3 days. 25 Treatment with BITRAP suppressed the mRNA expression of MMP9 and MMP13 compared with the Fc controls ( Figure 2E). Bitrap treatment also decreased the level of IFN-γ, but there was no statistical significance ( Figure 2D).…”
Section: Bitrap Inhibits the Production Of Inflammatory Cytokines Amentioning
confidence: 89%
“…To investigate whether BITRAP could modulate the cytokine level in Th17 cells, CD4 + T cells were cultured with BITRAP under Th17-polarizing condition for 3 days. 25 Treatment with BITRAP suppressed the mRNA expression of MMP9 and MMP13 compared with the Fc controls ( Figure 2E). Bitrap treatment also decreased the level of IFN-γ, but there was no statistical significance ( Figure 2D).…”
Section: Bitrap Inhibits the Production Of Inflammatory Cytokines Amentioning
confidence: 89%
“…e Relative AP-1 promoter luciferase reporter activity using fluorescent intensity. Gene expression of uPA, COL1A1, and MMP1 was evaluated using RT-qPCR with the 2 -ΔΔCt method and data presented were normalized to β-actin; *p ≤ 0.05 compared with irradiated cells without angelic acid treatment and #p ≤ 0.05 compared with negative control cells that were not treated with angelic acid and UVA irradiation Trypuć et al, 2016). Having views on those reports, we aimed at demonstrating whether angelic acid protects UVA-induced ECM decomposition as modulating gene expression which coded ECM proteins, uPA, COL1A1, and MMP1 especially.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is one of the main extracellular structural components which is responsible for structural integrity and stability with various biological functions like cell growth, differentiation, migration, and even skin aging (Ricard-Blum, 2011;Kim et al, 2017;Jabłońska-Trypuć et al, 2016;Quan et al, 2006). For the importance of structural proteins, especially diverse types of collagen, studies focused on understanding its regulating mechanisms have been pursued.…”
Section: Introductionmentioning
confidence: 99%
“…However, over time, the detrusor muscle becomes decompensated and then lower urinary tract symptoms (LUTS) appear, ultimately progressing to urinary retention with overflow incontinence [3,4].. Studies have shown that hypertrophy can be found in both smooth muscle cells and the extracellular matrix (ECM) of the bladder wall in BOO [5], where the ECM hypertrophy is mainly due to collagen accumulation, and the more collagen accumulates, the worse the LUTS are [6,7]. The main reason for collagen accumulation in the bladder wall in BOO is inhibited collagen catabolism rather than increased synthesis; this process is controlled by matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) [8,9]. An effective method for terminating or even reversing the morphological changes in the bladder wall is to relieve BOO as early as possible [3,4].…”
Section: Introductionmentioning
confidence: 99%